2000
DOI: 10.1021/bi992530h
|View full text |Cite
|
Sign up to set email alerts
|

Escherichia coli ATP Synthase α Subunit Arg-376:  The Catalytic Site Arginine Does Not Participate in the Hydrolysis/Synthesis Reaction but Is Required for Promotion to the Steady State

Abstract: The three catalytic sites of the F(O)F(1) ATP synthase interact through a cooperative mechanism that is required for the promotion of catalysis. Replacement of the conserved alpha subunit Arg-376 in the Escherichia coli F(1) catalytic site with Ala or Lys resulted in turnover rates of ATP hydrolysis that were 2 x 10(3)-fold lower than that of the wild type. Mutant enzymes catalyzed hydrolysis at a single site with kinetics similar to that of the wild type; however, addition of excess ATP did not chase bound AT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
38
1

Year Published

2001
2001
2013
2013

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 41 publications
4
38
1
Order By: Relevance
“…Analyzing mutant enzymes with Lys and Cys at position 376 of the a subunit, we concluded that aArg376 does not play a catalytic role, but is important for conformational transmission among the three sites, as discussed in detail previously (5,29). bGlu185 located near aArg376 in the catalytic site is also close to the phosphate moiety of ATP in the crystal structure (17).…”
Section: Mutational Studies On F-atpasesupporting
confidence: 59%
“…Analyzing mutant enzymes with Lys and Cys at position 376 of the a subunit, we concluded that aArg376 does not play a catalytic role, but is important for conformational transmission among the three sites, as discussed in detail previously (5,29). bGlu185 located near aArg376 in the catalytic site is also close to the phosphate moiety of ATP in the crystal structure (17).…”
Section: Mutational Studies On F-atpasesupporting
confidence: 59%
“…38 but see also ref. 39). This difference between the calculated contribution and that obtained from the mutation studies could be caused by several factors (13).…”
Section: Resultsmentioning
confidence: 79%
“…Le et al [63] also showed that αArg376 can be replaced and the F 1 enzyme retains the ability to carry out uni-site catalysis; however, the enzyme had essentially no cooperative steady state ATPase activity which involves all three sites. These results suggest that αArg376 may also be important to create the high affinity Pi binding site as β E converts to β DP during ATP synthesis (Fig.…”
Section: Partial Reaction and Rotation Steps In Steady Statementioning
confidence: 99%